PTPIP51, a positive modulator of the MAPK/Erk pathway, is upregulated in glioblastoma and interacts with 14-3-3β and PTP1B in situ - Petri, Meike Katinka; Koch, P.; Stenzinger, Albrecht; Kuchelmeister, K.; Nestler, U.; Paradowska, A.; Steger, K.; Brobeil, A.; Viard, M.; Wimmer, M. (Histology and histopathology, 2011)
Glioblastoma multiforme (GBM) is the most common and most malignant primary brain tumour. Protein tyrosine phosphatase interacting protein 51 (PTPIP51) is an interaction partner of 14-3-3β, which correlates with the grade of malignancy in gliomas. In this study PTPIP51 and its interacting partners 14-3-3β, PTP1B, c-Src, Raf-1 as well as EGFR were investigated in human glioblastoma. Twenty glioblastoma samples were analyzed on transcriptional and translational level by immunohistochemistry, in situ hybridization and RT-PCR. To compare PTPIP51 expression in gliomas of different malignancies, quantitative RT-PCR for grade II astrocytoma and GBM samples was employed. Additionally, we analyzed the correlation between PTPIP51 and 14-3-3β transcription, and checked for in situ interaction between PTPIP51 and 14-3-3β and PTP1B, respectively. PTPIP51 and 14-3-3β mRNA showed a tumour grade dependent upregulation in gliomas. Glioblastoma cells displayed a strong immunoreaction of PTPIP51, which co-localized with 14-3-3β and PTP1B. The duolink proximity ligation assay corroborated a direct in situ interaction of PTPIP51 with both proteins, known to interact with PTPIP51 in vitro. The in vitro interacting partners Raf-1 and c-Src showed a partial co-localization. Besides, immune cells located in capillaries or infiltrating the tumour tissue and endothelial cells of pseudoglomerular vessels revealed a high PTPIP51 expression. The upregulation of PTPIP51 and its connection with the EGFR/MAPK pathway by 14-3-3β via Raf-1 and by PTP1B via c-Src, argue for a functional role of PTPIP51 in the pathogenesis of human glioblastoma.